2011
DOI: 10.1097/sap.0b013e3181ea1e9b
|View full text |Cite
|
Sign up to set email alerts
|

Microdeformation of Three-Dimensional Cultured Fibroblasts Induces Gene Expression and Morphological Changes

Abstract: Microdeformations produced by the combination of polyurethane foam and suction are associated with increased fibroblast proliferation and up-regulation of gene expressions in fibroblasts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 21 publications
2
67
0
1
Order By: Relevance
“…This is because although GAB1 has been considered a major player for mediating the activation of the PI3K/AKT1 pathway by FGF via FGFRs [8,12,13], little is known regarding the proximal FGF/FGFR signaling mechanism that controls activation of the PI3K/AKT1 pathway. Our findings suggest that caveolae functions as a focal center for organizing the proximal FGF2/FGFR1 signaling via FRS2a in placental endothelial cells because: 1) FRS2a has a caveolin binding motif ( 65 YGYDSNLF 72 , aromatic amino acids underlined) [38] that is highly conserved among different species [40][41][42]; 2)…”
Section: Discussionmentioning
confidence: 99%
“…This is because although GAB1 has been considered a major player for mediating the activation of the PI3K/AKT1 pathway by FGF via FGFRs [8,12,13], little is known regarding the proximal FGF/FGFR signaling mechanism that controls activation of the PI3K/AKT1 pathway. Our findings suggest that caveolae functions as a focal center for organizing the proximal FGF2/FGFR1 signaling via FRS2a in placental endothelial cells because: 1) FRS2a has a caveolin binding motif ( 65 YGYDSNLF 72 , aromatic amino acids underlined) [38] that is highly conserved among different species [40][41][42]; 2)…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that tension can markedly alter fibroblast expression of matrix remodeling and inflammatory genes (Kessler-Becker et al, 2004;Derderian et al, 2005). Moreover, mechanical forces can induce fibroblast collagen production, a-smooth muscle actin expression, cytokine expression, and proliferation in vitro (Yang et al, 2004;Webb et al, 2006;Hinz et al, 2007;Lu et al, 2011), suggesting that mechanical tension is largely driven by fibroblast-mediated mechanisms. Keratinocytes, which form the initial barrier to the external world, are also mechanically responsive and are important regulators of skin activity.…”
Section: Mechanosensing Cells Of the Skinmentioning
confidence: 96%
“…Moreover, fibroblasts by regulating ECM homeostasis, control elasticity and strength of the tissue mechanical properties, that in turn influence fibroblast behavior. In 3D, such biochemical, mechanical and physical cues were also shown to be fundamental for sustaining cell homeostasis (Chiquet, 1999;Chiquet et al, 2003Chiquet et al, , 2009Farran et al, 2010;Hakkinen et al, 2011;Lu et al, 2011). The dynamic conditions as compared to the static ones creating a shear stress and/or fluid flow, can also regulate cell behavior either in 2D or in 3D (Kinney et al, 2011;Wang and Tarbell, 2000;Ng and Swartz, 2003;Shi and Tarbell, 2011).…”
Section: Discussionmentioning
confidence: 97%